GAMBARAN KEJADIAN TUBERKULOSIS PARU DI KABUPATEN BANYUMAS TAHUN 2004-2008 - Dwi Sarwani Sri Rejeki; Sri Nurlaela; Suratman Suratman (Kesmas Indonesia, 2010)
Indonesia places the third rank regarding tuberculosis cases in the world after India and China. Based on the result of a prevalence survey of Lung Tuberculosis in 2004, a national average prevalence rate of tuberculosis was 0.107%. Data of tuberculosis cases per 10.000 at Banyumas District Health Office from year 2003 until year 2005 consecutively were 1.1 in 2003, 3.7 in 2004, and 3.9 in 2005. Therefore, there needs to make a trend of a tuberculosis occurrence in order to improve the tuberclosis intervention program based on the real database. The objective of this research was to describe the occurrence of tuberculosis in Banyumas District from year until year 2008. Secondary data were obtained from Banyumas District Health Office. The result of this research showed that a number of clinical tuberculosis case in Banyumas District from year 2004 until year 2008 decreased, number of positive BTA cases increased, all cases of positive BTA had been treated, and part of cases had not been healed yet. The tuberculosis case in Banyumas District was an important health problem from year 2004 until year 2008. This condition was proved by data regarding positive BTA tuberculosis as a source of a transmission. The average of Case Detection Rate in Banyumas District was about 40-50% that was lower than the average of National Case Detection Rate (70%). Otherwise, Cure Rate was good enough (85%). As a suggestion, Head of Banyumas District Health Office and Health Centers should find a tuberculosis case both actively and passively and should increase cure rate through monitoring a behavior of drinking medicine on sufferers’ group